An integrated marketing communications campaign for Pure Nectar - Buenaventura, Marco Joaquin D. (Animo Repository, 2016)
This integrated marketing communications campaign is curated for Pure Nectar, a cold-pressed juice brand, a new-comer in the Philippine juice market. It was formally launched earlier in 2015 by its mother company, Fruit Magic. So far, the biggest challenge for the brand is spreading awareness among consumers. But with the increasing number of health-conscious and affluent millennials in the Philippines (Euromonitor, 2016), more and more consumers are looking for the healthier option. Hence, services like meal plan delivery and juicing became an instant hit among affluent consumers. However, competition remains competitive, given that most of its competitors have been in the market for quite some time. Furthermore, the trend among RTD juices positioning themselves as healthy beverages (Euromonitor, 2016) pose a threat to Pure Nectar and brands alike, given that these RTD juice brands are relatively priced lower compared to naturally healthy 100% fruit juice. In order to achieve the brands goals, Pure Nectars integrated marketing campaign will utilize a mixture of traditional and new media in order to communicate and engage with its consumers. The idea is not just to communicate the brands message to its audience, but for the consumers to experience the brand as well. Although it is relatively a small brand, growth rate since its launch has been promising, while its mother brands growth rate, started to decline. Having said that, Fruit Magic will act as financial support to Pure Nectars marketing campaign, to allow its newest brand to grow and penetrate the market. Together with its marketing objectives, the brand is expected to achieve a 10% increase in sales in 2017, with the help of this marketing campaign.